Long-Term Results of Modified Green Method in Sprengel’s Deformity - Gonen, Emel (Springer Berlin Heidelberg, 2010)
AIM: Congenital undescended scapula (Sprengel deformity) is a rare deformity that is reported in the literature mostly as small case series with short- or medium-term follow-up periods. Here, we aimed to present the long-term results of this deformity treated with modified Green procedure. METHOD: The modified Green procedure was performed in 24 patients (28 shoulders) with Sprengel deformity. Clavicular osteotomy accompanied in all, and omovertebral bone excision in 13 shoulders. The mean age of the patients at the time of surgery was 4.5 years (range 1.5–17 years). Mean follow-up period was 11 years 4 months (4.3–17 years). Preoperative cosmetic appearance was noted as Cavendish III in 17 shoulders and as IV in 11 shoulders. In addition to the Cavendish scale, shoulder abduction, shoulder asymmetry, and scapular elevation and medialization were evaluated. RESULTS: The decrease in scapular elevation and Cavendish scale, and the improvement in shoulder abduction and scapular medialization postoperatively were statistically significant (P < 0.001). Cosmetic improvement of at least one Cavendish grade were attained in 88.9% of shoulders. One patient (unilateral) who was Cavendish grade IV preoperatively died in the early postoperative period from unrelated causes. Of the remaining 10 preoperatively grade IV shoulders, 2 remained at the same grade, 1 improved to grade III, and 7 shoulders to grade I. Of the 17 preoperatively grade III shoulders, 1 shoulder stayed the at same grade, 7 shoulders improved to II, and 9 shoulders to grade I. Postoperative winging in 2 shoulders and hypertrophic scarring in 6 shoulders were noted. CONCLUSION: The modified Green procedure is a relatively safe and reliable method in the treatment of severe Sprengel deformity cases and provides highly constructive and aesthetic results in the long term.